Indeks Pembangunan Kesehatan Polri: Indeks Pembangunan Kesehatan Polri - Frans Tjahyono; Dwi Purwoko; Titin Siswantining (Jurnal Litbang Polri, 2024)
National Police health development is a long-term investment in the development of National Police personnel with the hope that it can play a role in increasing life expectancy and maintaining and improving their level of health so that they can carry out their main duties optimally in safeguarding and maintaining security and public order optimally. This research was conducted in 11 Polda and 96 Polres. Data collection was carried out by distributing questionnaires to all Civil Servants at the National Police, FGDs with key officials at the Regional Police and Regional Police, as well as FGDs with health workers at the National Police Polyclinic/FKTP. The results showed that the national percentage of PNPP health conditions was 29% (84,102 PNPP) obesity, 20.40% (58,997 PNPP) central obesity, the highest prevalence rate of PTM (Gastric, Heart Diabetes Mellitus and Stroke), the highest prevalence rate of PM (Diarrhea, Typus and Malaria). Nationally, around 0.7% (1,902 PNPP) SRQ-20 screening results indicated mild GME. A total of 0.15% (432 PNPP) indicated moderate GME, and 0.1% (292 PNPP) indicated heavy GME. Apart from that, there were also 0.07% (206 PNPP) who thought about committing suicide.